The Role of the Palestine Liberation Organization in Establishing the Foundations of Palestinian Diplomacy - HUMEID, MOHAMMED (İstanbul Kültür Üniversitesi, 2023)
This research thesis aims to clarify the role of diplomacy in giving legitimacy to liberation movements after it was limited to states only with their international legal personality in the international system, and by recognizing the international effectiveness of non-state persons to practice diplomatic work. The study also aims to clarify the role of the PLO in establishing the foundations of Palestinian diplomacy before moving to state diplomacy, as Palestinian diplomacy constituted a unique case as it was a precedent for the state. The PLO has practiced diplomatic work since its inception years, and opened diplomatic offices that formed the nucleus to support the contemporary Palestinian revolution, and to mobilize international support for the demand for national rights to independence, and the establishment of an independent Palestinian state. The importance of this research lies in its contribution to the formation of a comprehensive view of decision-makers when dealing with or developing political and diplomatic laws in the field of international relations in order to reach the fastest and most appropriate political solution regarding the Palestinian issue, which allows them to rely on it as one of the sources instead of having to start the search from the beginning to the end in order to make the best decision.
Filistin Kurtuluş Örgütünün Filistin Diplomasisinin Temellerini Oluşturmadaki Rolü
▪ Yüksek lisans tezi.
Keywords: Diplomacy; Palestine; PLO; International Relations